Risk and uncertainty in milk production by smallholders in Tanzania: Implications for inclusiveness and investment - Twine, Edgar E.; Omore, Amos O.; Githinji, J.W.K. (2017)
The study evaluates the impact of risk on enterprises of smallholder male, female and young milk producers in Tanzania’s formal and informal dairy value chains. It also examines the effect of uncertainty on the decision to invest in milk production in both value chains. Results indicate that youths in the informal value chain face the greatest level of risk followed by men in the formal value chain, and then men in the informal value chain. Women in both value chains and youths in the formal value chain face relatively low risk. Overall, milk production in the informal chain is found to be substantially riskier than production in the formal chain. Optimal investment triggers are found to be much larger than the conventional triggers and are sensitive to volatility of returns. The results’ policy and practical implications for inclusive dairy industry development in Tanzania are highlighted.